Tracking control of autonomous vehicles via backstepping method with dynamic surface control - Makoto YOKOYAMA; Koji NISHIKAWA (Mechanical Engineering Journal)
This paper discusses a trajectory tracking control problem for the development of autonomous vehicles. The reference trajectory is generated by a kinematic model which is nonholonomically constrained not to skid at the rear drive wheels. A nonlinear dynamical controller to follow the trajectory is proposed by applying backstepping (BS) method, together with Dynamic Surface Control (DSC) to solve the so called “problem of explosion of terms in the BS method”. Ultimate boundedness of the closed-loop system is investigated. Finally, simulation results illustrate the effectiveness of the proposed controller.